Acetylation mediates Cx43 reduction caused by electrical stimulation. (October 2015) - Meraviglia, Viviana; Azzimato, Valerio; Colussi, Claudia; Florio, Maria Cristina; Binda, Anna; Panariti, Alice; Qanud, Khaled; Suffredini, Silvia; Gennaccaro, Laura; Miragoli, Michele; Barbuti, Andrea; Lampe, Paul D.; et al.
Abstract: Communication between cardiomyocytes depends upon gap junctions (GJ). Previous studies have demonstrated that electrical stimulation induces GJ remodeling and modifies histone acetylase (HAT) and deacetylase (HDAC) activities, although these two results have not been linked. The aim of this work was to establish whether electrical stimulation modulates GJ-mediated cardiac cell–cell communication by acetylation-dependent mechanisms. Field stimulation of HL-1 cardiomyocytes at 0.5 Hz for 24 h significantly reduced connexin43 (Cx43) expression and cell–cell communication. HDAC activity was down-regulated whereas HAT activity was not modified resulting in increased acetylation of Cx43. Consistent with a post-translational mechanism, we did not observe a reduction in Cx43 mRNA in electrically stimulated cells, while the proteasomal inhibitor MG132 maintained Cx43 expression. Further, the treatment of paced cells with the HAT inhibitor Anacardic Acid maintained both the levels of Cx43 and cell–cell communication. Finally, we observed increased acetylation of Cx43 in the left ventricles of dogs subjected to chronic tachypacing as a model of abnormal ventricular activation. In conclusion, our findings suggest that altered electrical activity can regulate cardiomyocyte communication by influencing the acetylation status of Cx43. Highlights: Electrical activity modulates the acetylation/deacetylation balance of excitable cells. Electrical activity modulates the acetylation status of Cx43. Electrical activity modulates myocardial cell–cell communication through Cx43 acetylation.